0 голосов
1 просмотр

Решить 4 и 5 полностью с решением и проверкой


image
от (13 баллов) по предмету Алгебра

1 Ответ

0 голосов
от БОГ (228k баллов)
 
Лучший ответ

Ответ:

Объяснение:

4)

√(x²-3x+11)-4x²+12x=11

√(x²-3x+11)-4x²+12x-44=11-44

√(x²-3x+11)-4*(x²-3x+11)=-33

Пусть √(x²-3x+11)=t≥0   ⇒

t-4t²=-33

4t²-t-33=0     D=529      √D=23

t₁=-2,75 ∉

t²=3     ⇒

√(x²-3x+11)=3

(√(x²-3x+11))²=3²

x²-3x+11=9

x²-3x+2=0     D=1

x₁=2     x₂=1.

5)

[tex]\sqrt{\frac{2-x}{x-1} } -7*\sqrt{\frac{x-1}{2-x} } =6[/tex]            ОДЗ: x-1≠0    x≠1     2-x≠0     x≠2.

Пусть  [tex]\sqrt{\frac{2-x}{x-1} } =t[/tex]    ⇒

[tex]t-\frac{7}{t} =6\\t^{2} -6t-7=0\\D=64;\sqrt{D}=8\\[/tex]

t₁=7   t₂=-1  ∉      ⇒

[tex]\sqrt{\frac{2-x}{x-1} } =7\\(\sqrt{\frac{2-x}{x-1} } )^{2} =7^{2} \\\frac{2-x}{x-1} =49\\2-x=49*(x-1)\\2-x=49x-49\\50x=51|:51\\x=\frac{51}{50}.[/tex]

...